Principles of Arabic Language Curriculum Design - Fadhli Fakhrurrozi Furkony; Isop Syafei; Pajar Abdurahman; Ade Arip Ardiansyah (UIN Sunan Gunung Djati Bandung, 2025)
Learning Arabic is not just about memorizing vocabulary or understanding grammar, but requires a curriculum that is carefully designed to be able to answer the needs of students and adapt to the times. This study aims to discuss the main principles that must be the basis for compiling an Arabic curriculum, including the relevance of the material, continuity between levels, flexibility of content, and effectiveness and efficiency of implementation. This study uses a literature study method, the author examines various literature related to the design of the Arabic curriculum in Indonesia. The results of this study indicate that linguistic principles, communicative principles, attention to student needs, and a competency-based approach are key elements in creating a meaningful and contextual learning process. A curriculum built on these principles is believed to be more capable of supporting students in mastering Arabic actively and applicatively.